2021
DOI: 10.1177/03611981211002835
|View full text |Cite
|
Sign up to set email alerts
|

Use of Exclusive and Pooled Ridehailing Services in Three Mexican Cities

Abstract: The global expansion of ridehailing platforms has been accompanied by a diversification of service offerings as platforms fit within new urban contexts. While ridehailing has been of great interest to transportation researchers, analysis of its adoption and use in developing cities that differentiates between service offerings is lacking. To help address this knowledge gap, this study analyzes primary survey data collected from frequent users of the DiDi Chuxing ridehailing platform in three Mexican cities: Mé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…The results indicate that ride-hailing has decreased accidents and fatalities for all users, but mainly for female passengers, as well as among male drivers working at night. Finally, recent research in three Mexican cities (Mérida, Toluca de Lerdo, and Aguascalientes) focusing on exclusive and pooled services and using descriptive statistics from a survey to users of a Transportation Network Company operating in the country (Moody et al, 2021), shows that the share of males (67.7%) using express services is higher than the share of females (32.3%). Despite the handful of studies that have findings regarding how gender interplays with ride-hailing adoption, very few studies explore the role of gender and ride-hailing usage in depth in the Latin American or developing country context.…”
Section: Gender Transportation and Ride-hailing Researchmentioning
confidence: 99%
“…The results indicate that ride-hailing has decreased accidents and fatalities for all users, but mainly for female passengers, as well as among male drivers working at night. Finally, recent research in three Mexican cities (Mérida, Toluca de Lerdo, and Aguascalientes) focusing on exclusive and pooled services and using descriptive statistics from a survey to users of a Transportation Network Company operating in the country (Moody et al, 2021), shows that the share of males (67.7%) using express services is higher than the share of females (32.3%). Despite the handful of studies that have findings regarding how gender interplays with ride-hailing adoption, very few studies explore the role of gender and ride-hailing usage in depth in the Latin American or developing country context.…”
Section: Gender Transportation and Ride-hailing Researchmentioning
confidence: 99%
“…In the blue circle, the variables of a technological nature are observed, indicating that they belong to the 3 dimensions. The impact and importance of the technological characteristics of the offer and its ordering form are corroborated by Rangel et al, 2021;Shi et al, 2021. In turn, the reduced price and the expectation of benefits (red circle) indicate the utilitarian and individual character of the use, that is, the personal advantages associated with the cost are important drivers of use, which is corroborated by Moody et al, 2021;Violin, 2021a. Such elements distinguish this offer of public transportation modes, which has in its characterization price, time, boarding place and other passengers as variables that cannot be defined by consumers. This inference is echoed in studies such as those developed by the Fia Foundation; CAF, 2017 and Costa et al, 2021 and appear as relevant among the four use motivators listed above.…”
Section: Commonalitiesmentioning
confidence: 80%
“…The propensity of the population to avail of ride-hailing services stands out, whether in developed (Lavieri ;Bhat, 2019) or developing countries (Moody et al, 2021), indicating that it is a worldclass phenomenon, however, a limitation to be overcome is centered on the fact that a substantial part of the studies present only descriptive factors in their context of analysis, not establishing correlations with elements underlying the decision-making process to consume the service, such as the motivators of use -Work, Leisure, Social Obligations and Distinct Responsibilities -(Soto Villagrán, 2019) associated with periods of travel (morning, afternoon, night and dawn), pointing to a gap to be filled.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the descriptive analysis of 2019 survey data of California metropolitan areas, those who used TNCs at least once a week reported being more likely to consider pooling options from TNCs and engage in more multimodal trips (using a combination of TNCs and public transit to complete a trip) ( 1 ). A descriptive analysis of survey data of DiDi ridesourcing users in three Mexican cities during 2020 found that frequent use of ridesourcing is positively associated with public transit and privately operated buses, with important factors being safety, driver experience, and estimated travel time ( 47 ).…”
Section: Factors Affecting the Choice Of Poolingmentioning
confidence: 99%